The combination of intermittent caloric restriction and moderate-intensity interval training in decreasing blood glucose and CRP levels with a high glycemic index diet: DOI: 10.48129/kjs.12365 - Rif'at Fawaid As'ad, Muchammad; Meinar Sari, Gadis; Othman, Zulhabri; Herawati, Lilik (Kuwait Journal of Science, 2022)
This study aims to analyze the effect of the combination of intermittent calorie restriction and moderate intensity interval training (MIIT) on serum CRP levels as one of inflamatory mediator and blood glucose levels in female mice exposed to a high glycemic index diet. The sample of this study used female mice Balb/c strain, which were divided into 4 groups, the control group (Con), the intermittent calorie restriction group (Restrict), the MIIT group (Interv), and the combination group of intermittent calorie restriction and moderate intensity interval training (Restrict+Interv). A high glycemic index diet was a high calorie and provided by standard feed and oral gavage of 0.013 g/gBW glucose solution. Intermittent calorie restriction was 50% reduction of the standard feed 3x/week. The MIIT was 5-minute intervals of swimming and 30 seconds of passive rest consecutively for 30 minutes, 3x/week. The treatment duration was 4 weeks. Oral glucose tolerance test which consist of fasting blood glucose (FBG) and 2-hour post prandial blood glucose (2HPP) was measured before and after treatment. CRP was examined only after treatment. The restrict+interv group had a significant reduction in CRP levels compared to restrict (p=0.005) and interv group (p=0.044). There was a significant decrease in FBG levels between the restrict+interv with restrict group (p=0.026). There was also a significant decline in 2HPP between the restrict+interv with restrict group (p=0.000). The conclussion of this study was the combination of intermittent calorie restriction and moderate intensity interval training can affect serum CRP level and blood glucose levels diminution.